Methodical bases of investment strategies and portfolio management of modern industrial enterprises - E. V. Dmitrieva (Путеводитель предпринимателя, 2020)
Every industrial enterprise that is subject to medium and large businesses, creates its own investment strategy, which in turn presupposes the formation and elaboration of the same name portfolio. Efficiency of investment portfolio of industrial enterprise affects the performance of the enterprise as a whole and identifies key aspects of its development. The process of forming an investment portfolio requires careful planning and management. The paper presents the methodological foundation develop investment strategies of industrial enterprises and the basic methodological approaches to the formation and management of investment portfolio created in the framework of this strategy.